2018
DOI: 10.18632/oncotarget.23861
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant nimotuzumab plus chemoradiotherapy compared to neoadjuvant chemoradiotherapy and neoadjuvant chemotherapy for locally advanced esophageal squamous cell carcinoma

Abstract: Neoadjuvant therapy improves long-term locoregional control and overall survival after surgical resection for esophageal cancer, and neoadjuvant chemotherapy (nCT) or neoadjuvant chemoradiotherapy (nCRT) are commonly used in clinical practice. Nimotuzumab is a humanized monoclonal antibody against epidermal growth factor receptor (EGFR), the efficacy of nimotuzumab added to nCRT for esophageal cancer is uncertain. We conducted this retrospective study in which combining neoadjuvant treatment of nimotuzumab wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…However, several studies on the combination of neoadjuvant radiotherapy/chemotherapy with cetuximab have shown disappointing results, with no significant improvement in pCR rate, increased toxicity, and no clear survival benefit compared to neoadjuvant radiotherapy alone [69,70]. In contrast, the results of studies on the combination of neoadjuvant radio-chemotherapy with nimotuzumab seem more promising, and the use of nimotuzumab in combination with radio-chemotherapy improved R0 resection rate, pCR rate, and disease control rate (DCR), without significant increase in toxicity [71,72]. In addition, some studies have shown that for some esophageal adenocarcinoma patients with positive HER-2 expression, the use of trastuzumab, a HER-2 targeted therapy drug, in combination with radio-chemotherapy improved the pCR rate and R0 resection rate [73,74].…”
Section: Advancement Of Neoadjuvant Therapy In Ec Research Progress A...mentioning
confidence: 99%
“…However, several studies on the combination of neoadjuvant radiotherapy/chemotherapy with cetuximab have shown disappointing results, with no significant improvement in pCR rate, increased toxicity, and no clear survival benefit compared to neoadjuvant radiotherapy alone [69,70]. In contrast, the results of studies on the combination of neoadjuvant radio-chemotherapy with nimotuzumab seem more promising, and the use of nimotuzumab in combination with radio-chemotherapy improved R0 resection rate, pCR rate, and disease control rate (DCR), without significant increase in toxicity [71,72]. In addition, some studies have shown that for some esophageal adenocarcinoma patients with positive HER-2 expression, the use of trastuzumab, a HER-2 targeted therapy drug, in combination with radio-chemotherapy improved the pCR rate and R0 resection rate [73,74].…”
Section: Advancement Of Neoadjuvant Therapy In Ec Research Progress A...mentioning
confidence: 99%
“…The results showed that the addition of monoclonal antibodies was safe, the R0 resection rate reached 100%, and the pCR rate reached 41.2%. Compared with nCRT and nCT alone, the R0 resection and pCR rate, respectively, increased by 4.1% and 7.4%, and 8.8% and 26.4% [91]. In another phase I study, Qi et al [92] concluded that nimo combined with nCT (paclitaxel/carboplatin + 41.4Gy RT) had a favorable anti-cancer effect in locally resectable advanced EC with tolerable toxicities.…”
Section: Molecular Targeted Therapy Combined With Nct or Ncrtmentioning
confidence: 99%
“…6 A large number of studies are being conducted to explore new treatment modalities to improve the survival of patients with EC. 7,8 In recent years, immunotherapy has continuously made new breakthroughs in the treatment of various tumor types. 9,10 Immune checkpoint inhibitors have been used in a large number of clinical studies on EC and have achieved certain results.…”
Section: Introductionmentioning
confidence: 99%
“… 6 A large number of studies are being conducted to explore new treatment modalities to improve the survival of patients with EC. 7 , 8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation